2008
DOI: 10.1111/j.1365-2958.2008.06260.x
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral roles of eukaryotic frataxin: mitochondrial frataxin function and heterologous expression of hydrogenosomal Trichomonas homologues in trypanosomes

Abstract: SummaryFrataxin is a small conserved mitochondrial protein; in humans, mutations affecting frataxin expression or function result in Friedreich's ataxia. Much of the current understanding of frataxin function comes from informative studies with yeast models, but considerable debates remain with regard to the primary functions of this ubiquitous protein. We exploit the tractable reverse genetics of Trypanosoma brucei in order to specifically consider the importance of frataxin in an early branching lineage. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 63 publications
(107 reference statements)
0
43
0
Order By: Relevance
“…After the addition of tetracycline, which triggers RNAi, growth of the Tb-frataxin and Tb-IscS knock-down controls virtually stopped at day 5 postinduction (SI Appendix, Figs. S16 and S17), as, in the absence of these proteins, the cells cease dividing and eventually die (29,30). However, the procyclic trypanosomes in which RNAi-ablated Tb-frataxin was replaced by Bh-frataxin in trans retained almost the same growth as their noninduced counterparts (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After the addition of tetracycline, which triggers RNAi, growth of the Tb-frataxin and Tb-IscS knock-down controls virtually stopped at day 5 postinduction (SI Appendix, Figs. S16 and S17), as, in the absence of these proteins, the cells cease dividing and eventually die (29,30). However, the procyclic trypanosomes in which RNAi-ablated Tb-frataxin was replaced by Bh-frataxin in trans retained almost the same growth as their noninduced counterparts (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S16 and S17) indicates that Bh-frataxin and Bh-IscS plus Pt-Isd11 can partially replace the function of Tb-frataxin and Tb-IscS in the Tb mitochondrion. As previous studies have shown that the down-regulation of Tb-frataxin and Tb-IscS causes a disruption of Fe/S cluster assembly (29,36), it is likely that this function is provided in trans by the Blastocystis homologue. To verify this assumption, we measured activities of several previously described Fe/S cluster-containing enzymes with mitochondrial and/ or cytosolic localization (29,37).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations